Prove that \[\dfrac{{\sin \theta - \cos \theta + 1}}{{\sin \theta + \cos \theta - 1}} = \dfrac{1}{{\sec \theta - \tan \theta }}\]
Answer
Verified
512.4k+ views
Hint: Here R. H. S indicates a term which includes $\sec \theta $ so, we divide the numerator and denominator of L. H. S by $\cos \theta $.
Dividing numerator and denominator by $\cos \theta $ makes the L. H. S term easy. As $\sec \theta $ is reciprocal of $\cos \theta $ so we are dividing L .H .S by $\cos \theta $.
$ \Rightarrow $L. H. S = \[\dfrac{{\sin \theta - \cos \theta + 1}}{{\sin \theta + \cos \theta - 1}} \div \dfrac{{\cos \theta }}{{\cos \theta }}\]
$ \Rightarrow $L. H. S =$\dfrac{{\dfrac{{\sin \theta - \cos \theta + 1}}{{\cos \theta }}}}{{\dfrac{{\sin \theta + \cos \theta - 1}}{{\cos \theta }}}}$ ……. (1)
Now, by using trigonometric identities we will simplify the L. H. S term.
We know that
$\dfrac{{\sin \theta }}{{\cos \theta }} = \tan \theta $, $\dfrac{{\cos \theta }}{{\cos \theta }} = 1$, $\dfrac{1}{{\cos \theta }} = \sec \theta $
Now, putting these values in equation (1), we get
$ \Rightarrow $L. H. S = $\dfrac{{\tan \theta - 1 + \sec \theta }}{{\tan \theta + 1 - \sec \theta }}$ ……. (2)
Now, using the identity ${\sec ^2}\theta - {\tan ^2}\theta = 1$, equation (2) becomes simple. We replace the value of 1 only in the denominator to get the desired result.
Replacing value of 1 in denominator, we get
$ \Rightarrow $L. H. S =$\dfrac{{\tan \theta - 1 + \sec \theta }}{{\tan \theta - \sec \theta + ({{\sec }^2}\theta - {{\tan }^2}\theta )}}$
We know that $({a^2} - {b^2}) = (a - b)(a + b)$, using this property L. H. S can be written as,
$ \Rightarrow $L. H. S =$\dfrac{{\tan \theta - 1 + \sec \theta }}{{\tan \theta - \sec \theta + (\sec \theta - \tan \theta )(\sec \theta + \tan \theta )}}$
Taking $(\sec \theta - \tan \theta )$ common from denominator,
$ \Rightarrow $L. H. S =$\dfrac{{\tan \theta - 1 + \sec \theta }}{{(\sec \theta - \tan \theta )( - 1 + \sec \theta + \tan \theta )}}$
Now, eliminating the same terms from the numerator and the denominator, we get
$ \Rightarrow $L. H. S =$\dfrac{1}{{\sec \theta - \tan \theta }}$= R. H. S
Hence proved.
Note: To solve such problems one should have the knowledge of trigonometric identities like ${\sin ^2}\theta + {\cos ^2}\theta = 1$ , $se{c^2}\theta - {\tan ^2}\theta = 1$ and $\cos e{c^2}\theta - {\cot ^2}\theta = 1$ which are very useful in solving the problems. Another key point is that we have to see the R. H. S of the question to decide which identity we can use to solve the problem.
Dividing numerator and denominator by $\cos \theta $ makes the L. H. S term easy. As $\sec \theta $ is reciprocal of $\cos \theta $ so we are dividing L .H .S by $\cos \theta $.
$ \Rightarrow $L. H. S = \[\dfrac{{\sin \theta - \cos \theta + 1}}{{\sin \theta + \cos \theta - 1}} \div \dfrac{{\cos \theta }}{{\cos \theta }}\]
$ \Rightarrow $L. H. S =$\dfrac{{\dfrac{{\sin \theta - \cos \theta + 1}}{{\cos \theta }}}}{{\dfrac{{\sin \theta + \cos \theta - 1}}{{\cos \theta }}}}$ ……. (1)
Now, by using trigonometric identities we will simplify the L. H. S term.
We know that
$\dfrac{{\sin \theta }}{{\cos \theta }} = \tan \theta $, $\dfrac{{\cos \theta }}{{\cos \theta }} = 1$, $\dfrac{1}{{\cos \theta }} = \sec \theta $
Now, putting these values in equation (1), we get
$ \Rightarrow $L. H. S = $\dfrac{{\tan \theta - 1 + \sec \theta }}{{\tan \theta + 1 - \sec \theta }}$ ……. (2)
Now, using the identity ${\sec ^2}\theta - {\tan ^2}\theta = 1$, equation (2) becomes simple. We replace the value of 1 only in the denominator to get the desired result.
Replacing value of 1 in denominator, we get
$ \Rightarrow $L. H. S =$\dfrac{{\tan \theta - 1 + \sec \theta }}{{\tan \theta - \sec \theta + ({{\sec }^2}\theta - {{\tan }^2}\theta )}}$
We know that $({a^2} - {b^2}) = (a - b)(a + b)$, using this property L. H. S can be written as,
$ \Rightarrow $L. H. S =$\dfrac{{\tan \theta - 1 + \sec \theta }}{{\tan \theta - \sec \theta + (\sec \theta - \tan \theta )(\sec \theta + \tan \theta )}}$
Taking $(\sec \theta - \tan \theta )$ common from denominator,
$ \Rightarrow $L. H. S =$\dfrac{{\tan \theta - 1 + \sec \theta }}{{(\sec \theta - \tan \theta )( - 1 + \sec \theta + \tan \theta )}}$
Now, eliminating the same terms from the numerator and the denominator, we get
$ \Rightarrow $L. H. S =$\dfrac{1}{{\sec \theta - \tan \theta }}$= R. H. S
Hence proved.
Note: To solve such problems one should have the knowledge of trigonometric identities like ${\sin ^2}\theta + {\cos ^2}\theta = 1$ , $se{c^2}\theta - {\tan ^2}\theta = 1$ and $\cos e{c^2}\theta - {\cot ^2}\theta = 1$ which are very useful in solving the problems. Another key point is that we have to see the R. H. S of the question to decide which identity we can use to solve the problem.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE
Define least count of vernier callipers How do you class 11 physics CBSE